American gothic : new interventions in a national narrative - Martin, Robert K., 1941-; Savoy, Eric (University of Iowa Press, 1998)
Drawing widely on contemporary theory - particularly revisionist views of Freud such as those offered by Lacan and Kristeva - this volume ranges from the well-known Gothic horrors of Edgar Allan Poe and Nathaniel Hawthorne to the popular fantasies of Stephen King and the postmodern visions of Kathy Acker. Special attention is paid to the issues of slavery and race in both black and white texts, including those by Ralph Ellison and William Faulkner. In the view of the editors and contributors, the Gothic is not so much a historical category as a mode of thought haunted by history, a par.